Penerapan model pembelajaran direct instruction untuk meningkatkan keterampilan menulis deskripsi peserta didik kelas IV SD - Ami Nur Amini; St. Y. Slamet; Sukarno Sukarno (Universitas Sebelas Maret, 2024)
This research aims to: (1) determine whether the application of the direct instruction learning model can improve the description writing skills of fourth grade students at SD Muhammadiyah Imam Syuhodo Polokarto, (2) describe the application of the direct instruction learning model in improving the description writing skills of class students, (3) describes the results of improving the descriptive writing skills. This research uses research based on Classroom Action Research (PTK) with descriptive qualitative as the method. The subjects in this research were 27 students at class IV and their class teachers. Researchers use data collection techniques in the form of observation, interviews, document analysis, and test techniques. The data analysis method refers to the opinion of Miles & Huberman, namely data reduction, data presentation, and drawing conclusions. This research resulted in an increase in each cycle in learning descriptive writing skills using the direct instruction learning model. This was shown in the pre-action pass of 14.81% to 40.74% in cycle I, increasing again to 66.67% in cycle II. Then in cycle III it increased to 85.2%.